2020
DOI: 10.1007/s00170-020-05192-2
|View full text |Cite
|
Sign up to set email alerts
|

Laser-arc hybrid welding of 12- and 15-mm thick structural steel

Abstract: High-power lasers are very effective in welding of plates thicker than 10 mm due to the keyhole mode. High-power intensity generates a vapor-filled cavity which provides substantial penetration depth. Due to the narrow and deep weld geometry, there is susceptibility to high hardness and weld defects. Imperfections occur due to keyhole instability. A 16-kW disk laser was used for single-pass welding of 12-to 15-mm thick plates in a butt joint configuration. Root humping was the main imperfection and persisted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…For 12 mm thick plates, high root quality was achieved with 0.45 kJ/mm laser heat input and > 15 mm laser-arc distance. The humping is decreasing with increase laser-arc distance which is related decrease of melt flows velocities [22] and lower negative interaction between the processes [30,31]. Autogenous LBW provided better keyhole stability compared to LAHW; thus, higher quality of the root may be achieved.…”
Section: Discussion On Root Qualitymentioning
confidence: 95%
See 2 more Smart Citations
“…For 12 mm thick plates, high root quality was achieved with 0.45 kJ/mm laser heat input and > 15 mm laser-arc distance. The humping is decreasing with increase laser-arc distance which is related decrease of melt flows velocities [22] and lower negative interaction between the processes [30,31]. Autogenous LBW provided better keyhole stability compared to LAHW; thus, higher quality of the root may be achieved.…”
Section: Discussion On Root Qualitymentioning
confidence: 95%
“…1.2). This is related to unfavorable effect on melt flows providing strong momentum in the root [22] with poor process control due to keyhole instability. The same parameters were repeated for another 0.5 m long plate with significant adjustments in WFR reaching 16 m/min to form larger weld reinforcement.…”
Section: Welds With 20°bevelling Anglementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that focusing properties affected the weldability strongly during laser welding of the thick steel plate and that a long focus depth was particularly useful in producing sound welds. To overcome the fit-up issue, a common solution from process is to use a laser together with an arc to perform hybrid welding [33,34] that may be simply considered as arc melting the surface for the laser to initiate the interaction with the material.…”
Section: Process Innovationsmentioning
confidence: 99%
“…In addition, during the welding process GMAW applies a high heat input to the welding material, resulting in large heat-affected zones HAZs and occurrence of the undesired microstructure [6]. On the other hand, LBW provides deep and narrow welds at high welding speeds, due to its high energy density, leading to a small HAZ and low distortion [7]. However, the LBW process like any other process has disadvantages, one of them is high cooling rate from the welding zone that leads to high weld metal hardness and low toughness, which sometimes cannot meet the minimum mechanical properties [8].…”
Section: Introductionmentioning
confidence: 99%